Submandibular salivary gland ligation - Near-catastrophic post-operative complication - Imogen Scott; James Olsen; Rakesh Jattan (Elsevier, 2022)
A six-year-old child presented with airway obstruction requiring emergency tracheostomy secondary to infection in the remnant left Wharton's duct following SMG ligation. Whilst co-morbidities contributing to, and management of sialorrhea are well documented; near-catastrophic post-operative complications are not. We reflect on efficacy of surgical management in sialorrhea, and re-evaluate procedural morbidity.